Growing pains at Groupon - Dutta, Saurav; Caplan, D.; Marcinko, D. (American Accounting Association, 2014)
On November 4, 2011, Groupon Inc. went public with an initial market capitalization of $13 billion. The business was formed a couple of years earlier as an offshoot of "The Point." The business grew rapidly and increased its reported revenue from $14.5 million in 2009 to $1.6 billion in 2011. Soon after going public, prior to its announcement of its first-quarter results, the company's auditors required Groupon to disclose a material weakness in its internal controls over financial reporting that impacted its disclosures on revenue and its estimation of returns. This case uses Groupon to motivate discussion of financial reporting issues in ecommerce businesses. Specifically, the case focuses on (1) revenue recognition practices for "agency" type e-commerce businesses, (2) accounting for sales with a right of return for new products, and (3) use of alternative financial metrics to better convey the intrinsic value of a business. The case requires students to critically read, analyze, and apply authoritative accounting guidance, and to read and analyze communications between the Securities and Exchange Commission (SEC) and the registrant.